Stabilization of Pavement Granular Layer using Foamed and Emulsified Asphalt under Critical Low Temperature Conditions - Sánchez, J (2019)
One of the efficient techniques that is currently used in pavement engineering to improve the stress–strain response conditions of the pavement structure includes the stabilization of its structural layer components. There are several laying techniques that include the usage of stabilizing agents such as emulsified and foamed asphalt. In these technologies, the temperature of the environment is observed to play a critical role. This condition is often considered to be the main factor that encourages the usage of foamed asphalt for stabilization. Further, the aforementioned technique specifies that, at temperatures of approximately 10 °C or lower, the asphalt particles are not effectively inserted in the foamed granular material mastic; they are instead merged with other asphalt particles. This causes an agglomeration of coalesced asphalt, prevents adequate foaming, and hinders the pavement layer from compaction. In such a situation, the pavement will exhibit a structural strength deficiency. Therefore, this study experimentally investigates the environmental temperatures at which an efficient layer that is stabilized using foamed asphalt may be obtained both in the laboratory as well as in the field. Further, this study proposes a new limit. Apart from exceeding this temperature limit, the study also offers an alternative with respect to the usage of asphalt emulsions to stabilize the granular layer. This technique comprises the dispersion of asphalt particles in an aqueous medium; however, when this technique is applied at low temperatures, the low temperatures do not allow the system to reach a critical condition of inapplicability, which is observed when the asphalt foam is used for stabilization. Further, the mechanical behaviors of the foamed pavement at temperatures of lower than 10 °C are discussed. Additionally, this study exhibits the results of stabilized layers that use a slow-setting asphalt emulsion (CSS-1h) as a solution to the temperature problem that is associated with the usage of the foaming technique. The investigation is performed based on a project that is conducted in the extremely low temperature areas of the Peruvian Andean highlands, which are located at an altitude of 4,000 to 5,000 meters above the sea level.